The Rights of Families of Terminal Patients to Refuse Futile Treatment: Legal and Ethical Limitations - Primanto Tantiono; I Made Wirya Darma; I Gede Agus Kurniawan (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
Patients in terminal conditions are frequently subjected to futile medical interventions, namely treatments that no longer provide therapeutic benefits and merely prolong the biological process of life without improving its quality. This situation creates a dilemma between the family’s right to refuse such interventions and the physician’s professional obligations bound by ethical oaths and legal frameworks. In Indonesia, the regulation regarding the refusal of futile treatment by families of terminal patients remains ambiguous, leading to legal uncertainty and potential conflicts in healthcare practice. The purpose of this study is to analyze the legal boundaries governing the authority of families of terminal patients to refuse futile medical treatment and to examine medical ethical principles as the basis for legitimizing such rights. This research adopts a normative legal method with a conceptual approach, focusing on the study of legislation, legal doctrines, academic literature, and professional codes of ethics. The findings reveal that the legal foundation for the family’s authority to refuse futile treatment can be traced through the principle of informed consent as stipulated in the Medical Practice Act and the rights of patients in the Health Act. However, the absence of explicit regulation creates a wide scope for interpretation, which may trigger disputes. From an ethical standpoint, the family’s right to refuse futile interventions gains legitimacy through the principles of autonomy, beneficence, non-maleficence, and justice. The originality of this research lies in its integration of normative legal analysis with medical ethics principles, emphasizing the urgency of establishing specific regulations to ensure legal certainty while safeguarding patient dignity